2014
DOI: 10.1371/journal.pone.0089209
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Study on the Effects of Nisin on the Antibacterial Activities of 18 Antibiotics against Enterococcus faecalis

Abstract: Enterococcus faecalis rank among the leading causes of nosocomial infections worldwide and possesses both intrinsic and acquired resistance to a variety of antibiotics. Development of new antibiotics is limited, and pathogens continually generate new antibiotic resistance. Many researchers aim to identify strategies to effectively kill this drug-resistant pathogen. Here, we evaluated the effect of the antimicrobial peptide nisin on the antibacterial activities of 18 antibiotics against E. faecalis. The MIC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 46 publications
(52 reference statements)
8
68
0
5
Order By: Relevance
“…The DSSNϩ MIC for E. coli and S. oneidensis (64 M is approximately 100 mg liter Ϫ1 ) is not particularly high compared to antimicrobial MIMs, some of which can be active at concentrations in the g liter Ϫ1 range, and is roughly double that of magainin (16)(17)(18). Conversely, the toxicity of DSBNϩ and 4F-DSBNϩ for all organisms and, in particular, Gram-positive organisms (MIC for E. faecalis, Ϸ3 to 6 mg liter Ϫ1 ) is such that these compounds can be considered to have antimicrobial activity that is approaching a clinically interesting range and which is comparable with nisin and traditional ␤-lactams, like penicillin and imipenem (16,17). Aside from the differences in the toxicity profile based on the molecular characteristics, there is a difference in MIM toxicity that is determined by an organism's Gram status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DSSNϩ MIC for E. coli and S. oneidensis (64 M is approximately 100 mg liter Ϫ1 ) is not particularly high compared to antimicrobial MIMs, some of which can be active at concentrations in the g liter Ϫ1 range, and is roughly double that of magainin (16)(17)(18). Conversely, the toxicity of DSBNϩ and 4F-DSBNϩ for all organisms and, in particular, Gram-positive organisms (MIC for E. faecalis, Ϸ3 to 6 mg liter Ϫ1 ) is such that these compounds can be considered to have antimicrobial activity that is approaching a clinically interesting range and which is comparable with nisin and traditional ␤-lactams, like penicillin and imipenem (16,17). Aside from the differences in the toxicity profile based on the molecular characteristics, there is a difference in MIM toxicity that is determined by an organism's Gram status.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the outer membrane of Gram-negative organisms incorporates a negatively charged lipopolysaccharide (LPS) layer that acts as a molecular sieve, impeding the passage of small molecules across the cellular envelope. The protective effect of the Gram-negative OM to certain antibiotics is well documented (17,(22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the inevitable trend towards bacterial resistance, new approaches for killing and eliminating bacterial pathogens effectively as well as limiting the evolution of bacterial resistance are necessary. Nowadays, combinations of antibiotics is one important approach to improve the efficacy of antibacterial therapy and overcome resistance to an antibacterial agent (Afeltra, Vitale, Mouton, & Verweij, 2004;Oo, Cole, Garthwaite, Willcox, & Zhu, 2010;Tong et al, 2014). Antimicrobial combination therapy may be used to extend spectrum coverage, prevent the emergence of resistant mutants and gain synergy between antimicrobials (Eliopoulos, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies have demonstrated synergistic relationships between conventional antibiotics and nisin. The majority of these studies have involved Gram-positive bacteria such as staphylococci, including methicillin-resistant forms (Piper et al, 2009; Dosler and Gerceker, 2011; Okuda et al, 2013), enterococci (Tong et al, 2014), including vancomycin-resistant enterococci (Brumfitt et al, 2002), and streptococci (Lebel et al, 2013). Nisin-antibiotic combinations have also been shown to be effective against Gram-positive bacterial biofilms (Okuda et al, 2013; Field et al, 2015c).…”
Section: Introductionmentioning
confidence: 99%